2018
DOI: 10.1159/000493098
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Durative Transfusion of Endostar Combined with Chemotherapy in Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Background: The overall survival (OS) in non-small cell lung cancer (NSCLC) is poor, with median OS of advanced NSCLC with standard systemic chemotherapy being reported at 13.6 months and the 5-year survival rate at less than 15%. Therefore, the aim of this study was to evaluate Endostar combined with chemotherapy in patients with advanced NSCLC. Methods: Data on 116 cases of pathologically confirmed stage IIIB-IV NSCLC were retrospectively collected. The control group was treated with chemotherapy combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Therefore, it is interesting to examine the results from a t-test using log-transformation of read counts following one of the four normalization methods. As expected, the results show there is no difference between the UQ and UQ-pgQ2 methods since the median scaling factor estimated for each gene across samples in UQ-pgQ2 was canceled while applying a t-test [50]. Although UQ/UQ-pgQ2 performed relatively better than TMM and RLE, with a specificity of 48.7%, there was a tradeoff with lower power of 93.1%, consistent with previous reports [36,37].…”
Section: Statistical Analysis Of Maqc2 and Maqc3 For The Combined Metsupporting
confidence: 89%
“…Therefore, it is interesting to examine the results from a t-test using log-transformation of read counts following one of the four normalization methods. As expected, the results show there is no difference between the UQ and UQ-pgQ2 methods since the median scaling factor estimated for each gene across samples in UQ-pgQ2 was canceled while applying a t-test [50]. Although UQ/UQ-pgQ2 performed relatively better than TMM and RLE, with a specificity of 48.7%, there was a tradeoff with lower power of 93.1%, consistent with previous reports [36,37].…”
Section: Statistical Analysis Of Maqc2 and Maqc3 For The Combined Metsupporting
confidence: 89%
“…Therefore, it is necessary to closely observe and monitor cardiac toxicity during Endostar administration. The cardiotoxicity of Endostar is reported to be slight and reversible; however, close observation of the heart rate, electrocardiogram, myocardial enzymology markers, and cardiac ultrasound of patients during such therapy is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in other fields have shown favorable feasibility of CIV Endostar. In the report by Li et al 18 advanced NSCLC treated with CIV Endostar combined with chemotherapy showed a significantly higher disease control rate (86.2% vs. 70.7%, P < 0.01), longer median PFS (six months vs. four months, P = 0.037) and median OS (17.5 months vs. 13.5 months, P = 0.034) compared with IV Endostar combined with chemotherapy. The trend seen in the single-center retrospective study by Cheng et al19 was similar to that in the report by Li et al Yao et al 20 retrospectively compared the efficacy of CIV Endostar to IV Endostar in advanced or metastatic lung squamous cell carcinoma, both combined with gemcitabine/cisplatin chemotherapy (GP regimen).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies in other fields have shown favorable feasibility of CIV Endostar. In the report by Li et al . advanced NSCLC treated with CIV Endostar combined with chemotherapy showed a significantly higher disease control rate (86.2% vs. 70.7%, P < 0.01), longer median PFS (six months vs. four months, P = 0.037) and median OS (17.5 months vs. 13.5 months, P = 0.034) compared with IV Endostar combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 93%